Pengaruh Tingkat Kesempatan Kerja, Dan Ip-Tik Terhadap Pengangguran Terdidik Lulusan Sma Dan Smk Pada Tahun 2015-2021 Di Pulau Sumatera - Antasa, Muhammad Rizky; Suparta, I Wayan (Economics and Digital Business Review, 2025)
This research aims to analyze the influence Employment Opportunity Level and the information and communication technology development index on educated unemployment of high school and vocational school graduates on the island of Sumatra from 2015 to 2021. This research uses several variables, namely the independent variable which consists of the Employment Opportunity Level (X1) and the information and communication technology development index (X2), as well as the dependent variable, namely educated unemployment of high school and vocational school graduates on the island of Sumatra in the 2015-2021 period. The data used is secondary data obtained from government agency websites and analyzed using the panel data regression method using the Eviews10 application. The research results show that the variable Employment Opportunity Level has a negative and significant influence on educated unemployment for high school and vocational school graduates on the island of Sumatra. This means that increasing the Employment Opportunity Level will reduce educated unemployment for high school and vocational school graduates. On the other hand, the information and communication technology development index variable has a positive and significant influence on educated unemployment for high school and vocational school graduates, which means that an increase in the information and communication technology development index will encourage an increase in educated unemployment for high school and vocational school graduates. It is hoped that the results of this research can become a reference for further research and enrich knowledge, especially in the study of educated unemployment on the island of Sumatra.